Report on Improved Agricultural Implements on India - Planning Commission (Planning Commission, 1966)
I have great pleasure in forwarding herewith the All-India Report of the agriculture Team on Improved Agricultural Implements. This is the last report of the Team based on the studies conducted by the Team in the States of Punjab, Madras, Mysore, Maharashtra, Himachal Pradesh, Bihar, Assam and Uttar Pradesh.
Agriculture Team Committee on Plan Projects Planning Commission